Gastric duplication in a teenager: A case report - O.V. Karaseva; R.T. Nalbandyan; P.V. Medinskiy; A. Yu Kharitonova; V.G. Bagaev; A.A. Gromova (Elsevier, 2024)
Introduction: A duplication cyst (DC) of the gastrointestinal (GI) tract is a rare developmental anomaly of the digestive system. The latency and variability of clinical manifestations hamper the physician's ability to make the correct diagnosis, often leading to a marked delay in diagnosing the disease. The patient in the current report repeatedly sought medical help for four years before the correct diagnosis was made. Case presentation: A 14-year-old boy was admitted to the emergency department complaining of abdominal pain and repeated vomiting. A more thorough history revealed that similar pain accompanied by vomiting of gastric contents had been periodically noted for the last four years. According to the parents, the boy has had a poor appetite throughout the period, resulting in minor weight loss. On physical examination, the patient's abdomen was not distended and could be examined with only moderate pain on deep palpation in the epigastric and right mesogastric regions. To exclude perforation of a hollow organ and intestinal obstruction, plain abdominal radiography in two standing projections was performed, which showed no free air under the diaphragm and no features characteristic of intestinal obstruction. Ultrasonography of the abdomen, in the area of the major curve of the stomach near the head and body of the pancreas, revealed a cystic mass with echogenic contents 40 × 30 mm in size. The patient underwent an esophagogastroduodenoscopy (EGD). In the antrum, along the posterior gastric wall, there was an ovoid-shaped mass measuring about 40 × 30 mm and covered with smooth pink mucosa. According to the MRI, there was a clearly outlined cystic mass, 38 x 36 × 40 mm in size. A complete examination allowed for the diagnosis of a gastric DC and a decision was made to perform laparoscopic surgery. The laparoscopy was performed under general anesthesia using the three-port technique. The duplication cyst in the stomach was removed laparoscopically. The course of the postoperative period was smooth. Conclusion: The latency and variability of clinical manifestations of gastric DC in children complicate the correct diagnosis and lead to a delay in definitive diagnosis. Modern imaging techniques allow for diagnosing rare GI pathology before surgery. Minimally invasive surgical techniques facilitate the early recovery of patients.